Attentional Processing of Disgust and Fear and Its Relationship With Contamination-Based Obsessive–Compulsive Symptoms: Stronger Response Urgency to Disgusting Stimuli in Disgust-Prone Individuals - Fink-Lamotte, Jakob; Widmann, Andreas; Sering, Konstantin; Schröger, Erich; Exner, Cornelia (Frontiers in Psychiatry, 2021)
Disgust has recently been characterized as a low urgent emotion, particularly compared to fear. The aim of the present study is to clarify whether behavioral inhibition during disgust engagement is characteristic of a low urgency emotion and thus indicates self-imposed attentional avoidance in comparison to fear. Therefore, 54 healthy participants performed an emotional go/no-go task with disgust- and fear-relevant as well as neutral pictures. Furthermore, heart rate activity and facial muscle activity on the fear-specific m. corrugator supercilli and the disgust-specific m. levator labii were assessed. The results partially support the temporal urgency hypothesis of disgust. The emotion conditions significantly differed in emotional engagement and in facial muscle activity of the m. levator labii as expected. However, contrary to our expectations, no differences between the emotion condi-tions regarding behavioral inhibition as well as heart rate change could be found. Furthermore, individuals with a higher trait disgust proneness showed faster reactions and higher activity of the m. levator labii in response to disgust stimuli. The results show that different trait levels influence atten-tional engagement and physiological parameters but have only a small effect on behavioral inhibition.